Identification of Belgian mosquito species (Diptera: Culicidae) by DNA barcoding. (15th September 2014) - Versteirt, V.; Nagy, Z. T.; Roelants, P.; Denis, L.; Breman, F. C.; Damiens, D.; Dekoninck, W.; Backeljau, T.; Coosemans, M.; Van Bortel, W.
Abstract Since its introduction in 2003, DNA barcoding has proven to be a promising method for the identification of many taxa, including mosquitoes (Diptera: Culicidae). Many mosquito species are potential vectors of pathogens, and correct identification in all life stages is essential for effective mosquito monitoring and control. To use DNA barcoding for species identification, a reliable and comprehensive reference database of verified DNA sequences is required. Hence, DNA sequence diversity of mosquitoes in Belgium was assessed using a 658 bp fragment of the mitochondrial cytochrome oxidase I (COI) gene, and a reference data set was established. Most species appeared as well‐supported clusters. Intraspecific Kimura 2‐parameter (K2P) distances averaged 0.7%, and the maximum observed K2P distance was 6.2% for Aedes koreicus. A small overlap between intra‐ and interspecific K2P distances for congeneric sequences was observed. Overall, the identification success using best match and the best close match criteria were high, that is above 98%. No clear genetic division was found between the closely related species Aedes annulipes and Aedes cantans, which can be confused using morphological identification only. The members of the Anopheles maculipennis complex, that is Anopheles maculipennis s.s. and An. messeae, were weakly supported as monophyletic taxa. This study showed that DNA barcoding offers a reliable framework for mosquito species identification in Belgium except for some closely related species.